2017
DOI: 10.18632/oncotarget.15213
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 up-regulation in melanoma increases disease aggressiveness and is mediated through miR-17-5p

Abstract: PD-L1 is expressed by a subset of patients with metastatic melanoma (MM) with an unfavorable outcome. Its expression is increased in cells resistant to BRAF or MEK inhibitors (BRAFi or MEKi). However, the function and regulation of expression of PD-L1 remain incompletely understood.After generating BRAFi- and MEKi-resistant cell lines, we observed marked up-regulation of PD-L1 expression. These cells were characterized by a common gene expression profile with up-regulation of genes involved in cell movement. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 42 publications
1
72
1
Order By: Relevance
“…In addition, miR-34a [110,111], miR-138-5p [112], miR-25-93-106b [113], and miR-217 [114] have been demonstrated to inhibit the expression of PD-L1, thereby increasing antitumor immunity and inhibiting multiple metastatic traits. In contrast, modulation of miR-17-5p [115] and miR-197 [116] has been shown to be crucial for protumor function. Other types of ncRNAs, including lncRNAs and circRNAs, have also been reported to be involved in the regulation of the PD-1/PD-L1 pathway.…”
Section: Perspective: Ncrnas As Potential Targets For Immunotherapiesmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, miR-34a [110,111], miR-138-5p [112], miR-25-93-106b [113], and miR-217 [114] have been demonstrated to inhibit the expression of PD-L1, thereby increasing antitumor immunity and inhibiting multiple metastatic traits. In contrast, modulation of miR-17-5p [115] and miR-197 [116] has been shown to be crucial for protumor function. Other types of ncRNAs, including lncRNAs and circRNAs, have also been reported to be involved in the regulation of the PD-1/PD-L1 pathway.…”
Section: Perspective: Ncrnas As Potential Targets For Immunotherapiesmentioning
confidence: 97%
“…For example, recent studies reveal that blockade of miR-23a restored adoptive T cell transfer therapy providing new insights into improvement of immunotherapy efficacy [106]. Meanwhile, ncRNAs involved in the regulation of the PD-1/PD-L1 pathway may have a major role in limiting effective cancer immunity [110][111][112][113][114][115][116][117].…”
Section: Perspective: Ncrnas As Potential Targets For Immunotherapiesmentioning
confidence: 99%
“…PD-L1 overexpressing melanoma have been shown to be resistant BRAFi and MEKi. Audrito et al [63] demonstrated that miR-17-5p binds to PD-L1, suggesting its role in the resistance to targeted therapies.…”
Section: The Advent Of Immune Checkpoint Inhibitors: Do Mirnas Have Amentioning
confidence: 99%
“…Hence, miRNAs that specifically control one-target checkpoints are favored in biomarker development. Various miRNAs such as miR-34a, miR-17-5p, miR-15b, miR-193a-3p, miR-197miR-200c showed correlation with expression of PD-L1 in tumor tissues as well as in sera or plasmas, and purposed to have predictive values in ICBs therapy of different cancers (Chen et al, 2014;Cortez et al, 2016;Ahn et al, 2017;Audrito et al, 2017;Kao et al, 2017;Fan et al, 2019). In breast cancer, a panel of thirteen miRNAs has been identified that directly target and down-regulate B7-H3.…”
Section: Liquid Biopsies Biomarkersmentioning
confidence: 99%